Negotiating the Discourse of Equality in Adichie’s Fiction and Non Fiction - Egbedi, Martha Omotetobore (NIU Journal of Humanities, 2023)
Chimamanda Ngozi Adichie has shot herself to limelight because of her achievements as a writer, public intellectual, feminist activist, as well as being recognised as a fashion and beauty icon.  Her essays and interviews on different social media platforms have continue to encourage feminist discourses around the globe. She has also drawn severe criticisms for her feminist viewpoints of agitating equality for her African sisters from far-off and eliminating trans-women from her feminism. This article interrogates Adichie’s feminist philosophy in her fiction and nonfiction. It argues that women in her novels are not epitomes or defenders of the feminism promoted in her essays, but are relegated to the margins of culture and patriarchal abuse; shattering the basis of feminism in her nonfiction. Drawing instances from some of   her novels and nonfictional works, this paper concludes that Adiche’s fiction and nonfiction showcase dissimilar feminist world views. Keywords: Adichie, Feminism, Fiction, Nonfiction, Equality, Gender. Americanah